Molecular Diversity of Arbuscular Mycorrhizal Fungi (AMF) Associated with Carissa edulis, an Endangered Plant Species along Lake Victoria Basin of Kenya - Benard O. Ogoma; Stephen F. Omondi; Jane Ngaira; Josephine W. Kimani (International Journal of Forestry Research)
Carissa edulis is a tropical plant belonging to the family Apocynaceae. The species is widely used in the preparation of various herbal medicines. Earlier works in Kenya show that an aqueous extract from the roots of C. edulis has remarkable anti-herpes simplex virus. Due to its medicinal value, the species has been overexploited in its natural range and requires conservation interventions. Studies show that the species has beneficial relationships with arbuscular mycorrhizal fungi (AMF) that can enhance restoration of its population; however, no study has been undertaken to document the diversity of these AMF species. This study evaluated the genetic diversity of AMF associated with the roots of C. edulis within Lake Victoria basin ecosystem of Kenya. A cross-sectional, laboratory-based prospective study was carried out from roots of C. edulis collected from six sites within the ecosystem. Root samples were collected from 6 points (replicates) per site. AMF was assessed through morphological characterization and sequencing of small subunit of ribosomal DNA. Morphological identification identified four genera of AMF (Gigaspora, Acaulospora, Scutellospora, and Glomus) with no significant difference among the sites. Molecular analysis also revealed presence of four genera, but only two (Glomus and Acaulospora) were common for both the analyses with Glomus as the most predominant genera. In all the sites, there were large numbers of spores both in soil and in the roots confirming the association between C. edulis and AMF.